Soybean Maturity Group Choices for Early and Late Plantings in the Midsouth. (1st September 2014) - Salmeron, Montserrat; Gbur, Edward E.; Bourland, Fred M.; Buehring, Normie W.; Earnest, Larry; Fritschi, Felix B.; Golden, Bobby R.; Hathcoat, Daniel; Lofton, Josh; Miller, Travis D.; Neely, Clark; Shannon, Grover; et al.
Abstract : Growing conditions in the U.S. Midsouth allow for large soybean [ Glycine max L. (Merr.)] yields under irrigation, but there is limited information on planting dates (PD) and maturity group (MG) choices to aid in cultivar selection. Analysis of variance across eight (2012) and 10 (2013) locations, four PD, and 16 cultivars (MG 3–6), revealed that the genotype by environment (G×E) interaction accounted for 38 to 22% of the total yield variability. Stability‐analysis techniques and probability of low yields were used to investigate this interaction. Planting dates were grouped within early‐ and late‐planting systems. Results showed that MG 4 and 5 cultivars in early‐planting systems had the largest average yields, whereas for late‐planting systems, late MG 3 to late MG 4 cultivars had the largest yields. Least square means by MG within planting systems at each environment showed that MG 4 cultivars had the greatest yields or were not significantly different from the MG with the greatest yields in 100% of the environments for both early‐ and late‐planting systems. Yields of MG 5 cultivars were similar to those of MG 4 in 100% of the environments with an early planting but only in 20% of the environments with a late planting. The MG 3 cultivars were the best second choice for late plantings, with similar yields to MG 4 cultivars in 55 to 75% of the environments. These results have profound implications for MG recommendations in irrigated soybean in the U.S. Midsouth and indicate the need to reconsider common MG recommendations.